The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nano10050931
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Microwave Absorption Bandwidth in Graphene-Encapsulated Iron Nanoparticles with Core–Shell Structure

Abstract: Graphene-encapsulated iron nanoparticles (Fe(G)) hold great promise as microwave absorbers owing to the combined dielectric loss of the graphene shell and the magnetic loss of the ferromagnetic metal core. Transmission electron microscopy (TEM) revealed transition metal nanoparticles encapsulated by graphene layers. The microwave electromagnetic parameters and reflection loss (R) of the Fe(G) were investigated. Graphene provided Fe(G) with a distinctive dielectric behavior via interfacial polarizations taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…In the same range, figure 2a Raman frequency (cm −1 ) vibration assignment references 99 A g [68,72] . same D and G bands in the binary V 2 O 5 @C-R 2 HS/GF composites which were observed at 1335-1350 cm −1 and 1577.2-1581 cm −1 , respectively [76]. The D and G peaks in the Raman spectrum of the binary V 2 O 5 @C-R 2 HS/GF composites are narrower and more pronounced than that of the V 2 O 5 @C-R 2 HS due to the additional contribution of the GF in the materials.…”
Section: Results and Discussion (A) Structural Morphological And Textural Propertiessupporting
confidence: 62%
See 1 more Smart Citation
“…In the same range, figure 2a Raman frequency (cm −1 ) vibration assignment references 99 A g [68,72] . same D and G bands in the binary V 2 O 5 @C-R 2 HS/GF composites which were observed at 1335-1350 cm −1 and 1577.2-1581 cm −1 , respectively [76]. The D and G peaks in the Raman spectrum of the binary V 2 O 5 @C-R 2 HS/GF composites are narrower and more pronounced than that of the V 2 O 5 @C-R 2 HS due to the additional contribution of the GF in the materials.…”
Section: Results and Discussion (A) Structural Morphological And Textural Propertiessupporting
confidence: 62%
“…The D peak is linked to the disorder or defect in the graphitic structure while the G peak is ascribed to the tangential vibration of the sp 2 carbon atoms [75]. In the same range, figure 2a Raman shift (cm −1 ) [76]. The D and G peaks in the Raman spectrum of the binary V 2 O 5 @C-R 2 HS/GF composites are narrower and more pronounced than that of the V 2 O 5 @C-R 2 HS due to the additional contribution of the GF in the materials.…”
Section: Results and Discussion (A) Structural Morphological And Textural Propertiesmentioning
confidence: 93%
“…These structures are conducive to extending the propagation path of EM waves, enhancing multiple reflection loss (RL) and interfacial polarization, providing more polarization centers and reducing complex permittivity in order to balance the impedance matching. The typical microstructure of EMI shielding and absorbing materials includes segregated structure, [36] “brick and mortar” structure, [37] core‐shell structure, [38] and porous aerogel [39] . The preparation strategies and EM properties will be expatiated as follows.…”
Section: A Brief Knowledge For Emi Shielding/absorbingmentioning
confidence: 99%
“…22,23 For example, Che et al have filled Fe into carbon nanotubes by catalytic pyrolysis; 24 Li et al have synthesized rose-like carbon-wrapped iron (Fe@C) with a porous structure; 25 and Zhang et al have reported graphene-encapsulated iron nanoparticles by arc discharge. 26…”
Section: Introductionmentioning
confidence: 99%